Acute Vision Loss Secondary to Epidural Blood Patch: Terson Syndrome. Issue 1 (March 2017) - Pagani-Estévez, Gabriel L.; Chen, John J.; Watson, James C.; Leavitt, Jacqueline A.
Abstract : ( Reg Anesth Pain Med. 2016;41(2):164–168) Postdural puncture headache is commonly treated by lumbar epidural blood patch (EBP). A case study of vision loss that immediately occurred after an EBP is presented.